Soyinka's Language - Ofoego, Obioma (Book collections on Project MUSE., 2016)
This book explores in depth the uses of language in Wole Soyinka's plays, poetry and prose. The author approaches Soyinka's works through meticulous close readings, giving the writer his due by capturing the complexities, ambiguities, and nuances of his language.